Results from Colombia's 2018 report card on physical activity for children and youth (2018)
Physical activity (PA) promotion across the lifespan is a key strategy for the prevention of non-communicable diseases in the public health agenda in Colombia.1 However, the sparse national data available before 2015 indicated that PA levels among Colombian adolescents were low and sedentary behaviors were highly prevalent.2 As a result of the improvement in national surveillance, Colombia has national data on PA-related indicators for all ages between 5 and 17 years, for the first time. These data informed the third version of the Report Card on Physical Activity (Figure 1). The purpose of this article is to summarize the methodology and results of the Colombian 2018 Report Card on Physical Activity for Children and Youth.